Alcune fonti dell’antropologia di San Tommaso (seconda parte) - Izquierdo Labeaga, L.C., José A. (Alpha Omega, 2018)
Summary: The article wants lo track down the sources of S. Thomas Aquinas 'anthropology, pointing out the studies available on the subject. After an introduction on the open mentality and methodology of Thomas who tries lo synthesize the truth listening lo things and listening to men, the article distinguishes between "scientifìc" and "sapiential" sources. Among the scientifìc sources it notes the aristotelian (Aristotle, commentators, averroist discussion) and platonic elementes (Plato, Platonic, De Causis) and some smaller currents such as stoicism and epicureanism, inviting a more profund investigation of the medicai elements (Hippocrates, Aristotle, Galen, Avicenna). Among the sapiential sources il studies the Christian-biblical elements, highlighting the anthropological treatises of Gregorius Nissenus, Nemesius Emesenus and Johannes Damascenus, then considering the injluences of Augustin and the Magistri (Petrus Lombardus and Albertus Magnus). The appendix introduces a list with ali the authors quoted by Thomas.